Sistem Informasi Berbasis Web Sebagai Media Promosi Pada Toko Sinar Baru Grande Prabumulih - Valentine, Lola (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
A web-based information system as a promotional medium is a system that provides information services in the form of promotions. The researcher's aim is to make it easier to promote goods. The research objectives resulted in several uses consisting of practical and academic uses. The method used in this research uses a quantitative approach that is descriptive in nature to describe and describe a variable, symptom, situation or certain social phenomenon and the Waterfall development method, the analytical tools used are Use case diagrams, Class diagrams, Activity diagrams. . This information system was built to make it easier for consumers to view the latest products more easily and quickly.